Human-centered security in practice: evidence from Y-FIT Ghana on privacy, trust, and youth engagement in health technology system HIV prevention - Gloria Aidoo-Frimpong; Abass Tando Abubakar; Eric Owusu (Frontiers in Computer Science, 2026)
Health technology systems (HTS) increasingly mediate health-related communication and decision-making, yet security is often conceptualized primarily as a technical property rather than as a socially situated user experience. This study examined how adolescents and young adults in Ghana imagined, prioritized, and articulated requirements related to privacy, trust, and safe digital engagement in HIV prevention contexts. Data were drawn from the Open Call phase of the Y-FIT Ghana study, a national crowdsourcing initiative involving 103 youth aged 15–24 years. Of the submissions received, 72 that proposed digital or digitally mediated strategies for HIV prevention and care were included in the analysis. Using qualitative content analysis, we identified recurring patterns in participants' proposed strategies and design expectations. Participants consistently prioritized privacy and confidentiality as conditions they associated with anticipated willingness to engage, particularly because of stigma, social visibility, and fear of unintended disclosure. Trust was linked to peer influence, relatable communication, cultural resonance, transparency, and non-judgmental interaction rather than to institutional authority alone. Participants also favored systems that supported discreet access, simplified communication, anonymous questioning, and guided service navigation. Because the data comprised proposed strategies rather than observed system use, the findings should be interpreted as youth-generated perceptions and anticipated engagement rather than demonstrated behavior. The findings suggest that human-centered security in stigma-sensitive digital health settings should extend beyond technical safeguards to incorporate social exposure, relational trust, usability, and culturally responsive design.